Applications of Helical‐Chiral Pyridines as Organocatalysts in Asymmetric Synthesis. Issue 1 (22nd November 2012) - Peng, Zhili; Takenaka, Norito
ABSTRACT: A new family of chiral pyridines has been designed and synthesized for use in asymmetric organocatalysis. Thus, helical‐chiral pyridines induce high enantioselectivity in a range of mechanistically unrelated, synthetically significant transformations, including Friedel‐Crafts alkylation with nitroalkenes, periselective Diels‐Alder reactions with nitroalkenes, the ring‐opening of epoxides with a chloride nucleophile, and the propargylation of aldehydes.